2011
DOI: 10.1007/s10157-011-0436-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal paradoxical embolism in a hypertensive young adult without acute ischemic symptoms

Abstract: A 22-year-old woman, who often carried heavy books, was admitted for evaluation of hyperreninemic hypertension. Two months prior to admission, she noted leg edema. Radiological examinations revealed bilateral renal infarction with no other abnormal findings. An echocardiography showed a patent foramen ovale (PFO). Hypertension was considered secondary to renal infarction caused by paradoxical embolism through PFO. Antihypertensive and anticoagulant therapy led to improvement of hypertension. In previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Such cases accounted for only 2.9% of the referrals to a specialised centre for the evaluation of PFO 5. Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases accounted for only 2.9% of the referrals to a specialised centre for the evaluation of PFO 5. Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…18 There are a few small studies and case reports that have reported paradoxical embolism to the non-cerebral circulation causing limb ischemia, splanchnic ischemia, and splenic or renal infarction. [19][20][21][22][23][24][25][26][27][28] Almost exclusively the case reports suggest suspected the base ≥15 mm and an excursion with an amplitude ≥15 mm. A PFO was defined as the appearance of microbubbles across the interatrial septum (with or without the Valsalva maneuver) after intravenous contrast injection and the absence of a color Doppler jet, indicating a left-toright shunt.…”
Section: Retrospective and Prospective Studiesmentioning
confidence: 99%
“…Post-operative pain from renal infarction has been recently reported, but in this case arose from thrombus formation in a resected pulmonary vein stump and hence, not a true paradoxical emboli [6]. Only a limited number of paradoxical renal emboli have been reported and usually present as spontaneous, not post-operative, abdominal pain [7], [8], [9]. PFO occurs in 25–35% of the population and is usually asymptomatic but can cause cryptogenic stroke, migraine, platypnea-orthodeoxia syndrome and air embolism during decompression sickness in divers [10].…”
Section: Discussionmentioning
confidence: 73%